PERANAN ORANG TUA DALAM KEGIATAN BELAJAR ANAK USIA SEKOLAH 6-12 TAHUN DI LINGKUNGAN RT. 10/ RW. 001 KELURAHAN SEMUNAI KECAMATAN PINGGIR KABUPATEN BENGKALIS - Yusiani, Novia Dania; Sumardi, Sumardi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrac: The aim of this study was to find out in the RT the role of parents in the learning activities of school-aged children aged 6-12. 10 / RW. 001 Semunai Village, Pinggir Sub-District, Bengkalis Regency. This study uses a descriptive method with a quantitative approach. The sample in this study was 20 for questionnaire surveys and 40 for survey questionnaires with saturated sampling techniques in which all populations were sampled. The technique to collect data using a questionnaire. Techniques for data analysis using the percentage formula. The results of this study indicate that encouragement (motivation) is very good, supervising children's learning at home is classified as good, giving a good example is good, filling in learning facilities is classified as good. The four indicators of the role of parents in combination are then classified as good.Key Words: Role Of Parents, Learning Activities, Children Aged 6-12.